Leaf Gas Exchange, Chlorophyll Fluorescence, and Fruit Yield in Hot Pepper (Capsicum anmuum L.) Grown Under Different Shade and Soil Moisture During the Fruit Growth Stage - Juan-juan ZHU; Qiang PENG; Yin-li LIANG; Xing WU; Wang-lin HAO (Journal of Integrative Agriculture, 2012)
Relative leaf chlorophyll (Chl.) content, leaf gas exchange, Chl. fluorescence, plant biological biomass, and fruit yield were evaluated in growing hot pepper (Capsicum annuum L.) during the fruit-growing stages in hot summer under three shade levels (un-shade, 30% shade, and 70% shade) and four soil water contents (SWC) of 40–55%, 55–70%, 70–85%, and 85–100% of field moisture capacity (FMC). Hot pepper crops were more affected by light irradiance than by soil moisture and by their interaction during the whole observed periods. Hot pepper attained greatest relative leaf Chl. content (expressed as SPAD value) and photosynthetic activity when cultivated with 30% shade, resulting in the highest plant biological biomass and fruit yield. Although 70% shade improved leaf photosynthetic efficiency (expressed as Fv/Fm or Fv'/Fm'), crops obtained the lowest photosynthetic rate, photochemical quenching coefficient (qP), and non-photochemical quenching coefficient (NPQ). This showed that light irradiance was insufficiency in S70% (70% shade) treatment. The leaf net photosynthetic rates (PN), Fv/Fm, and fruit yield increased gradually as SWC levels increased from 40–55% to 70–85% FMC, but decreased as SWC was higher than 70–85% FMC. The water consumption increased progressively with SWC levels, but water-use efficiency (WUE) was the highest when soil moisture was 55–70% FMC. Interaction of shade and soil moisture had significant effects on PN and Fv/Fm, but not on other parameters. Under drought stress (40–55% and 55–70% FMC), 30% shade could relieve the droughty damage of crops and improve photosynthetic capacity and WUE, but 70% shade could not, oppositely, aggravate the damage. The positive correlation (r2 =0.72) between leaf PN and fruit yield was existent. This indicated that improvement of leaf photosynthesis would increase potentially marketable yield in hot pepper crops during the full fruit-growing stages. For agricultural purposes, approximately S30% (30% shade) with 70–85% FMC is suggested to cultivate hot pepper during the fruit growth stage in hot summer months.